Epidemiology of acute Chagas Diseases in Brazil from 2007 to 2018 (Research, Society and Development, 2020)
Objective: to analyze the panorama of Acute Chagas Disease, in order to elucidate issues related to the incidence in Brazilian regions over the years, in addition to bringing information on the theme, interrelating social determinants to aspects relevant to public health. Methodology: This is a descriptive epidemiological study, based on data from the Notifiable Diseases Information System, of the notified cases of this disease in the period from 2007 to 2018. The rates were calculated in the statistical program R, version 3.6.3. Results: In the study period, 2,708 confirmed cases of Acute Chagas Disease were recorded in the country, with an annual average of 225.33 cases, with a higher incidence in the years 2016 and 2018 (1.71 and 1.73 cases per 100,000 inhabitants, respectively). The highest incidence rates over the years occurred in the North Region, where it presents 94.87% of the total cases. The most affected individuals were males (53.6%), aged 20 to 39 years (33.4%), and brown (n = 2059, 76%). Conclusion: In view of this, the analysis of epidemiological data was extremely important, as they allow the observation that despite governmental initiatives aimed at preventing this disease in different regions of Brazil, especially in the North, where the incidence is still high.